Pemberian Pupuk Hayati Cair Berformulasi dan NPK Terhadap Pertumbuhan Bibit Tanaman Kakao (Theobroma cacao L.) di Medium Subsoil Ultisol - Imran Maruli Tua Sihombing; Fifi Puspita; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to know response of interaction between liquid biofertilizer formulatied and NPK manure and also to get the best combination treatment on the growth of caccao seedling in subsoil medium of ultisol. The research has been conducted at Experimental Garden of Agriculture Faculty University of Riau from      April to September 2017. Using completely randomized design, consisted of two  factor with three replication. The first factor was liquid biofertilizier formulated  with three level. and the second factor was NPK manure with four level. Data      were statistically analyzed using analysis of variance and the means were              compared with Duncan's New Multiple Range Test (DNMRT) at level 5%.The      result shows that the interaction between biofertilizier formulated and  NPK         manure increase the growth of caccao seedling in subsoil medium of ultisol. The  combination between biofertilizier of palm oil mill waste water formulating          35 ml/seed and 3,75 g/seed gave the best response in increasing plant height,        number of leaves and root length of caccao seedling. Keywords : cacao, biofertilizier, NPK.